PENGARUH PENILAIAN ETIKA TERHADAP PERILAKU MAHASISWA FAKULTAS TARBIYAH DAN KEGURUAN - Dwi Putri Musdansi; Rosa Murwindra; Helbi Akbar (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
This research is a quantitative study that aims to analyze the effect of ethical judgment on student behavior at the Kuantan Singingi Islamic University (UNIKS). The population used was students of the Tarbiyah and Teaching Faculty (FTK) with the sampling technique. Random sampling used SPSS. Data collection techniques use secondary data sources and pimer, for independent variables using secondary data sources by directly requesting the FTK UNIKS archive center, while the dependent variable uses primary data sources obtained directly from the original source through the Behavior scale. The test statistic needed to test the hypothesis is the correlation coefficient between the test score as a predictor and the score of a criterion. The interpretation of the analysis results in predictive studies is based on the betha index (β) or the b score in the regression model obtained. From the results of the study it was concluded that there was an effect of ethical judgment on the behavior of FTK UNIKS students with sig = 0.00 and F = 50.524, Y = 31.5 + 0.645X